Co-design to understand the tracheostomy product experiences of long-term tracheostomy users. Issue 2 (3rd July 2017) - Dickson, C.; Reay, S. D.; Douglas, R.; Nakarada-Kordic, I.
ABSTRACT: Tracheostomy product designs have barely changed in 100 years. Furthermore, there is limited research into the experiences of people living with long-term tracheostomy. Existing tracheostomy designs focus on minimizing costs and maintaining clinical function, often at the expense of user experience. Because tracheostomy user numbers are relatively small, their needs are overlooked despite the significant impact on their everyday lives. In response, this research aimed to capture tracheostomy users' stories, advocate for greater consideration of their needs and challenge historic stagnation in tracheostomy design. Co-design workshops were used to give tracheostomy users a voice, build a better understanding of the daily challenges they face and explore the complex relationships they have with their tracheostomy products. Research findings were captured in a series of critical design artefacts intended to evoke empathy for users' experiences and highlight problems with existing tracheostomy products. The research highlights aspects of tracheostomy user experiences requiring further research, sets a precedent for future design-led research in this area and makes a compelling case for tracheostomy product design innovation. The critical design artefacts are part of ongoing work concerning the design of tracheostomy products, and will be used to build support for improving tracheostomy users' experiences.